Organizational Drivers of Performance Information Use: The Perspective of Polish Local Governments - Mateusz Lewandowski (Transylvanian Review of Administrative Sciences, 2019)
Performance management systems have been widely implemented in local governments and deliver performance information (PI) to enhance organizational learning and control. However, such information is not often used. This study examines the relations between the organizational factors that affect performance information use. The study employs the theories of information systems to distinguish the quality and usefulness of performance information from other organizational drivers of the use of performance information. Based on survey data from Polish local governments, the study searches for potential mediators of PI use by testing the relations between the most influential organizational capabilities that drive PI use. The findings suggest that there is a link between the quality and usefulness of performance information, and that other organizational capabilities that drive PI use are independent from quality and usefulness of PI. The study contributes to knowledge of how performance information is used in public organizations in a CEE country.